AMPAK RESTRUKTURISASI TERHADAP KEPUASAN KERJA, KOMITMEN ORGANISASI DAN INTENSI KELUAR SURVIVOR. - Nur Wening (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2005)
Restructuring is suspected to be influencing perception of job insecurity. The jobinsecurity will have a negative impact on job satisfaction, organization commitment, and even turnover intention. When insecurity is conceived within someone’s perception, it will lower his or her job satisfaction and also commitment on the company. This research was conducted upon service (bank) and manufacturing companies which had run restructuring in the last four years. It involved 216 respondents with 78.2% of response rate. Simple regression and hierarchical regression analysis were used to analyze the data.An interesting finding of this research is that restructuring conducted in bank andmanufacturing companies has been found out to be having no influence on turnover intention. On the other hand, job insecurity perception does not influence job satisfaction, commitment, and turnover intention. In addition, this research came to a conclusion that organization commitment is an mediating variable between job satisfaction and turnover intentionKeywords: restructuring, job insecurity, job satisfaction, organization commitment, turnover intention, survivor.